Սյունյաց Շուշան իշխանուհու նվիրատվական և շինարարական գործունեությունը - Շաբունց, Գ.
Жена князя Ашота княгиня Шушан выделялась своей благотворительной и строительной (созидательной) деятельностью. Из ее строительной деятельности известно строительство 5 церквей монастыря Каркопа или Хотакерац в 910 году, а из благотворительной деятельности известно, что она подарила Татевскому монастырю Дзацард и Каратнис. В историографии есть упоминание о даре Шушаник Мрванских ларьков. The princess Shoushan, Prince Ashot’s wife was famous for her charitable and constructional activity. From her constructional activity it is notable to mention the construction of the five churches of Qarkop or Khotakerats Monastery in 910. She also donated Tsatsard and Qaratnis to Tatev Monastery. There is another record about Shoushan’s donation of koughpaks /the old name of stalls/ of Mirvan.
Keywords: Պատմություն